MARX ET CO REVISITED. REPRESENTATIONS OF THE ECONOMY IN RALF ANDTBACKA’S WUNDERKAMMER (2008) - Malmio, Kristina (The Nordic Journal of Aesthetics, 2020)
The present article studies the representation of economy in Wunderkammer (2008), a collection of poetry by Finland-Swedish author Ralf Andtbacka. Going back to the historical form of cabinets of curiosities, Wunderkammer depicts acts of buying, selling, and collecting. By showing the connectivity of objects and their impact on human subjects, Andtbacka actualizes and deconstructs topics originally initiated by Karl Marx, such as value, fetish, commodifica-tion, and alienation. The portrayal of capitalism, both past and pres-ent, in the book is highly ambivalent. On the one hand, collecting functions as a critical, anticapitalistic act. On the other hand, eco-nomic discourse has invaded the text and turned the author into a writing machine powered by the energy of neoliberal labor. Besides an excess of objects, the poems display an overflow of information, a characteristic feature of a postcapitalist economy. As an exam-ple of cognitive mapping, Wunderkammer allegorically portrays humans, objects, and information in the middle of a paradoxical economic transformation.